2001
DOI: 10.1016/s0735-1097(00)01127-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of myocardial perfusion during graded coronary artery stenoses by intravenous myocardial contrast echocardiography

Abstract: The degree of blood flow mismatch between ischemic and normal myocardial regions during graded coronary stenoses can be estimated in the dog by quantitative assessment of myocardial perfusion produced by IV myocardial contrast echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 22 publications
3
21
0
2
Order By: Relevance
“…It has been demonstrated that MCE not only closely agrees with single photon emission computed tomography (SPECT) [2,3] and positronemission tomography [4] but also enhances sensitivity of two-dimensional echocardiography (2DE) to detect obstructive International Journal of Cardiology 136 (2009) 47 -55 www.elsevier.com/locate/ijcard coronary artery disease (CAD) [5][6][7][8][9]. This higher incremental value of MCE over 2DE is explained by the discrepancy between perfusion and wall motion abnormalities (WMAs) in the ischemic cascade [5,7,8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 54%
“…It has been demonstrated that MCE not only closely agrees with single photon emission computed tomography (SPECT) [2,3] and positronemission tomography [4] but also enhances sensitivity of two-dimensional echocardiography (2DE) to detect obstructive International Journal of Cardiology 136 (2009) 47 -55 www.elsevier.com/locate/ijcard coronary artery disease (CAD) [5][6][7][8][9]. This higher incremental value of MCE over 2DE is explained by the discrepancy between perfusion and wall motion abnormalities (WMAs) in the ischemic cascade [5,7,8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 54%
“…[3][4][5][6] Recently, the development of contrast agent and ultrasonographic equipment technology, such as second harmonic imaging or intermittent triggered imaging, enabled intravenous myocardial contrast echocardiography in both animal experiments [1][2][3][4] and human studies. [5][6][7][8][9] Analysis of the contrast effect in myocardial contrast echocardiograms has been performed by the visual assessment of myocardial opacification 1,[7][8][9][10][11][12][13] and/or quantitative assessment of pixel intensity. 2,3,[6][7][8][9]14,15) Shapiro, et al 16) reported the reproducibility of quantitative myocardial contrast echocardiography using repeated intracoronary injections of contrast material in an animal study.…”
Section: Discussionmentioning
confidence: 99%
“…Mit den neuen kontrastspezifischen Ultraschallverfahren wird erstmals auch die direkte Beurteilung der Myokardperfusion im Echolabor realisierbar (Abbildungen 10 und 11). Das Potential der Myokardkontrastechokardiographie ist durch eine Vielzahl von tierexperimentellen und klinischen Untersuchungen mit intrakoronaren Kontrastmittelapplikationen eindrücklich belegt [45][46][47]. So lassen sich die Größe eines Myokardinfarkts, die Reperfusion bzw.…”
Section: Myokardkontrastechokardiographiework In Progressunclassified
“…"No-Reflow"-Phäno-men mittels der Kontrastechokardiographie erlangt werden. Bei Stenosen kann die hämodynamische Relevanz mittels der Kontrastechokardiographie beurteilt werden [47]. Mittlerweile wird die intraarterielle Injektion von Ultraschallkontrastmitteln erfolgreich in spezialisierten Zentren zur Bestimmung der "Area at Risk" bei Septalast-Okklusion bei der hypertrophen obstruktiven Kardiomyopathie eingesetzt [48].…”
Section: Myokardkontrastechokardiographiework In Progressunclassified